Perilaku Adopsi Teknologi Pada Era Digital - Nurul, Euis; Afif, Ahmad Sururi; Tambunan, Resman Muharul (Lembaga Dongan Dosen, 2024)
The rapid development of information and communication technology has created an increasingly connected world, facilitating access to information, and accelerating the process of interaction and transactions in various sectors. In this context, individual behavior, including consumer behavior, has undergone significant changes. The adoption of technology and the integration of digital lifestyles have created new behavioral patterns that are not only influenced by basic needs, but also by the stimuli generated by the digital ecosystem. Adoption of behavior in the digital era involves a complex process that involves understanding the various factors that influence individuals in using technology. SMKN 8 Jakarta, as one of the vocational education institutions, is at the forefront of educating students to be able to adapt to the development of the times and technology. To solve the problems faced by students at SMKN 8 Jakarta related to the behavior of adopting technology in the digital era, this community service program provides a solution, namely; holding training aimed at improving students' digital literacy. The community service program at SMKN 8 Jakarta runs effectively through five systematic stages: identification of needs, material development, training sessions, mentoring programs, and feedback evaluation